Fresh versus frozen embryo transfer for full-term singleton birth: a retrospective cohort study - Junwei Zhang; Mingze Du; Zhe Li; Lulu Wang; Jijun Hu; Bei Zhao; Yingying Feng; Xiaolin Chen; Lijun Sun (Journal of Ovarian Research, 2018)
Abstract Background Improvements in vitrification and frozen embryo transfer (FET) technologies have rapidly increased, and some evidence suggests that FET may increase pregnancy rates and lead to more favourable perinatal outcomes. However, the outcome of interest should be offspring safety. Therefore, the primary objective of our study was to investigate whether FET was preferable to fresh embryo transfer (ET) in terms of full-term neonatal birthweight and congenital malformations. Methods This was a retrospective cohort study of patients with no pregnancy-related complications who underwent first fresh ETs (n = 2059) or FETs (n = 2053), resulting in full-term singletons births. Outcome measures were neonatal birthweight, low birthweight (LBW), small-for-gestational age (SGA), large-for-gestational age (LGA), macrosomia and congenital malformations. Additionally, we used logistic regression to adjust for baseline characteristics (age, BMI, No. of embryos transferred and embryo stage) between the two groups. Results The mean neonatal birthweight was higher for singletons born after FET than for singletons born after fresh ET (3468.7 ± 475.3 vs. 3386.7 ± 448.1; p < 0.001). The frequencies of full-term singleton LBW and SGA after FET were significantly lower than those after fresh ET (1.7% vs. 3.0 and 4.4% vs. 6.7%, respectively), with adjusted rate ratios of 0.59 (95% CI, 0.37 to 0.98; p = 0.026) and 0.73 (95% CI, 0.55 to 0.99; p = 0.041), respectively. FET resulted in higher frequencies of macrosomia and LGA (15.1% vs 10.2 and 22.8% vs. 17.5%, respectively) than fresh ET, with adjusted rate ratios of 1.43 (95% CI, 1.16 to 1.75; p = 0.001) and 1.26 (95% CI, 1.07 to 1.49; p = 0.007), respectively. Furthermore, the incidence of congenital malformations was not different between the two groups (1.2% vs. 0.9%), with a rate ratio of 0.288. Conclusions After the cycles with pregnancy-related complications were excluded and after adjustments for baseline characteristics, women undergoing FET were associated with a higher neonatal birthweight than women undergoing fresh ET cycles. Additionally, the FET protocol was associated with lower rates of LBW and SGA and higher rates of macrosomia and LGA than the fresh ET protocol. Meanwhile, no difference in the congenital malformation rate was evident between the two groups.